Mediating role of Work Engagement on the influence of Job Resources and Public Service Motivation on affective commitment in employees in Parakita Dental and General Clinic - Fahruddin, Fahruddin; Jusni, Jusni; Aswan, Andi (PT. Riset Press International, 2023)
This study aims to examine the mediating role of work engagement in the relationship between job resources, public service motivation, and affective commitment in employees in the Parakita Dental and General Clinic environment. The population of this study is the employee agencies in the region, with a sample unit of individuals working in the agency. Non-probability sampling technique with purposive sampling was used in sampling, with a total of 100 respondents who had worked overnight for two years as research respondents. Data were obtained through a survey using a six-point Likert scale questionnaire, and data analysis was conducted using the SPSS version 25 program as well as the Sobel test as a tool to test the role of mediation. The results show that the importance of job resources and public service motivation in increasing work engagement, which in turn has an impact on employees' emotional attachment and desire to contribute maximally to the organization. By understanding the mediating role of work engagement, organizational management can design more effective strategies to improve work quality and employee engagement, and create a work environment oriented towards good public service values in the public sector.